Gamifikasi TikTok Meningkatkan Pemasaran Digital untuk UMKM: Peluang, Ludic Loop, dan Dimensi Etis - Mufid, Amjad Ismail (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2026)
Short video platforms like TikTok provide significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to optimize their digital marketing. A highly effective approach in this ecosystem is gamification, which is proven to enhance consumer engagement and loyalty. However, the integration of TikTok's algorithms and gamification strategies risks creating a ludic loop—a repetitive cycle of actions and rewards that can trigger addictive behaviors. This article aims to examine the impact of TikTok's gamification features, such as hashtag challenges and live streaming, on the marketing effectiveness of MSMEs while highlighting the ethical implications. Utilizing a literature review method grounded in Self-Determination Theory and Uses and Gratifications Theory, this study synthesizes two main findings. First, gamification significantly escalates brand awareness and accelerates sales conversions through the live commerce ecosystem. Second, this mechanism is prone to exploiting user psychology if designed without ethical boundaries. As a practical contribution, this study formulates a strategic framework for MSMEs to implement productive gamification. This framework balances commercial effectiveness with social responsibility, enabling MSMEs to leverage the ludic loop without exploiting consumer vulnerabilities.